v.1 - Maiti, Prasenjit (ed.) (New Delhi, 2007)
The Volumes cover an extensive range of critical areas that have one common theme of questioning the accepted parameters of development from different angles influenced by multiple academic backgrounds. An attempt has been made to accommodate conflicting points of view that would facilitate the reader to arrive at his/her own understanding of the problems under purview. Contributors to these Volumes have tried to argue the different issues and concerns of development paradigms. Their chapters indicate the different choices of development that are necessarily context-bound and issue-driven in approach. Choices entail alternatives from among a range of viable options that tend to determine and influence development projects. Both primary and secondary stakeholders are required under the imperatives informed by the project to choose among this or that in order to optimize their given baskets of utilities. Development projects more often than not involve the politics of choice that is underpinned by the who gets what, how, when, where and why scenario. These Volumes will be of interest to social and natural scientists, civil servants, policy-makers, environmentalists, economists, ecologists, civil society organizations, think tanks, non-government organizations and development consultants.
Keywords: Economic development